Analysis of implicit differential equations via Ψ-fractional derivative. Issue 7 (2nd October 2020) - Harikrishnan, S.; Elsayed, E. M.; Kanagarajan, K.
Abstract: In this paper, we discuss the existence, uniqueness and stability of implicit differential equation with Ψ -fractional derivative. The arguments are based upon Schauder fixed point theorem, Banach contraction principle and Ulam stability.